Persepsi Mahasiswa terhadap Literasi Media dan Disinformasi di Media Sosial - Miftahul Jannah; Ardoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the perceptions of students of the Library and Information Science Study Program, Padang State University, intakes of 2021 and 2022, regarding media literacy and disinformation on social media. The rampant problem of disinformation in the digital era demands critical thinking skills so that media users are able to sort out the truth of the information received. This study used a quantitative approach with a descriptive method. The study population was 191 students. The sample size was determined using the Slovin formula with a 10% error rate, resulting in 66 respondents. The sampling technique used simple random sampling, and the research instrument was a Likert-scale questionnaire that had been tested for validity and reliability (α = 0.908). The results showed that students' perceptions of media literacy and disinformation were in the very good category with an average score of 3.49. The expectation indicator obtained the highest score of 3.63, followed by attitude with a score of 3.57, motivation with a score of 3.45, experience with a score of 3.44, and interest with a score of 3.36. These findings indicate that students have a high awareness of the importance of media literacy as a bulwark against disinformation on social media. Students also demonstrated positive motivation and experiences in applying media literacy skills, although interest in formal educational activities still needs to be improved. This research confirms that media literacy has become a real necessity for the younger generation in creating a healthy, critical, and responsible social media culture.